USE OF GROWTH CHAMBERS FOR CABBAGE BREEDING - L. L. Bondareva; O. A. Razin (Овощи России, 2015)
Use of the growth chambers for cabbage breeding allows the reducing of certain stages of the breeding process and the growing biennial varieties of cabbage in a one-year cycle. In these growth chambers, the nutritional conditions, temperature, and lighting of plants are under control; the open pollination is eliminated.